Motivating residents to volunteer for urban waterway restoration: A segmentation approach - Zack Dorner; Lynette J. McLeod; Taciano L. Milfont; Philip Stahlmann‐Brown; Donald W. Hine; Robbie D. C. Maris; Jane C. Kitson; Natasha A. Tassell‐Matamua (Conservation Science and Practice)
Abstract Urban landscapes play a crucial role in the health of freshwater ecosystems. The task of protecting and restoring urban freshwater waterways requires concerted efforts from all sectors of society, including volunteers. The recruitment and retention of volunteers is often a challenge for community environmental organizations as urban residents are diverse and influenced by a blend of personal, societal, and environmental factors. We surveyed a representative sample of 1901 urban residents across Aotearoa New Zealand and used the Behaviour Change Wheel framework and audience segmentation to understand the underlying factors influencing volunteering for waterway restoration projects and to identify potential target audiences to recruit new volunteers. We identified four segments within the target audience (“Supportive,” “Receptive but unsure,” “Hesitant and lack opportunity,” and “Reluctant”) each with its own unique profile of capabilities, opportunities, and motivations for volunteering. Recommendations for appropriate intervention designs to increase levels of volunteering include providing tailored messaging and events for those who are “Receptive but unsure” or “Hesitant and lack opportunity” and information about volunteering opportunities to “Supportive” individuals. This knowledge lays the groundwork for future initiatives focused on increasing urbanites' volunteering with community freshwater restoration groups.